2022
DOI: 10.1186/s12876-022-02443-2
|View full text |Cite
|
Sign up to set email alerts
|

Establishing correlations between normal pancreatic and submandibular gland ducts

Abstract: Background The objectives of this study were to evaluate the relationship between ductal morphometry and ramification patterns in the submandibular gland and pancreas in order to validate their common fractal dimension. Methods X-ray ductography with software-aided morphometry were obtained by injecting barium sulphate in the ducts of post-mortem submandibular gland and pancreas specimens harvested from 42 adult individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Fractal properties [19] The first item analyzed was the length of Wharton's duct, defined intraglandularly as the largest canal extending from the pole of the gland to the extraglandular portion of the duct. The average total duct lengths were 63.8 ± 10.2 mm and 61.8 ± 8.9 mm for the right and left glands, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Fractal properties [19] The first item analyzed was the length of Wharton's duct, defined intraglandularly as the largest canal extending from the pole of the gland to the extraglandular portion of the duct. The average total duct lengths were 63.8 ± 10.2 mm and 61.8 ± 8.9 mm for the right and left glands, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, researchers investigated the relationship between ductal morphometry and ramification patterns in the submandibular gland and pancreas to confirm their shared fractal dimension[ 62 ]. The study found that while the length of the intraglandular submandibular duct and the main pancreatic duct were correlated, other morphometric features of the ducts were not.…”
Section: The Fractal Nature Of the Gastrointestinal Systemmentioning
confidence: 99%
“…A computer-aided morphometric method employing fractal geometry and Delaunay triangulation was introduced to quantify the necro-inflammatory phase in liver biopsy specimens. The method was applied to two-micrometer thick sections from 78 chronic hepatitis C virus-infected patients, immunohistochemically treated to identify inflammatory cells[ 62 ]. An automatic image analysis system was used to define the inflammatory cell network based on Delaunay triangulation, and the cells were categorized geometrically into clusters or irregular distributions within the tissue.…”
Section: The Fractal Nature Of the Gastrointestinal Systemmentioning
confidence: 99%
“…We have carried out a comparative study of the size of the human submandibular glands and pancreas, by the use of computer-aided planimetry of matched postmortem ductograms, revealing a strong correlation between both submandibular glands and pancreas, and no significant differences in size of the left vs. right submandibular gland (Stimec et al, 2018). Further, instigated by the fractal dimensions of the pancreatic and salivary glands, we undertook a correlative study on their ductal morphology and morphometry, including maximal caliber and length of the main duct, number of primary side branches/affluents and presence of eventual ductal tortuosities (Stimec et al, 2022). Significant correlations were found for length of the main duct and partly for the side branches.…”
Section: Salivary Gland and Pancreas -Gross Anatomy As Wellmentioning
confidence: 99%